Unlocking the Value of Small and Medium Enterprises - Taha, Ahmed (AUC Knowledge Fountain, 2021)
The role of small and medium enterprises (SMEs) in economic growth and development is an undeniable fact in the global economy. In emerging and developed economies, SMEs may contribute to more than 90% of the total enterprises. These businesses are a dominant source of job creation, innovation and growth foundation stemming from their competitive structure, technological adaptability and resilience to economic crises. Despite their significant contribution to the economic development and growth, there is not sufficient research that covers SMEs’ financial activity, liquidity, profitability and valuations. In this thesis, I introduce an Electronic Valuation Platform that provides a sufficient research coverage report on any selected SME in order to help filling the gap between investors and the SME markets. The hypothesis under testing is about validating the output fair value of tested SMEs from the Electronic Valuation Platform (EVP) relative to reports published by research houses and analysts. The deviations between the EVP empirical results and the professional output have been insignificant in most of the case studies. I have selected nine firms for testing, Prime Speed Medical, Raya Contact Center from Egypt; Comer Industries, Fervi SpA, Intred SpA, Powersoft SpA, Labomar, Portobello and Kolinpharma from Italy’s Alternative Investment Market (AIM).